2022
DOI: 10.34172/apb.2023.036
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Undecylenoyl Phenylalanine Loaded-Nanostructure Lipid Carriers (NLCs) as a New α-MSH Antagonist and Antityrosinase Agent

Abstract: Purpose: The aim of this study was to characterize the undecylenoyl phenylalanine (Sepiwhite (SEPI))-loaded nanostructured lipid carriers (NLCs) as a new antimelanogenesis compound. Methods: In this study, an optimized SEPI-NLC formulation was prepared and characterized for particle size, zeta potential, stability, and encapsulation efficiency. Then, in vitro drug loading capacity and the release profile of SEPI, and its cytotoxicity were investigated. The ex vivo skin permeation and the anti-tyrosinase activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Afterward, the desired pre-emulsion was sonicated using a sonicator probe (Bransonic, USA) in 7 cycles of 60 s with a rest time of 15 s between each cycle. Finally, the suspension was allowed to cool naturally at room temperature over 24 h, facilitating the formation of NLC/SLN without the need for external cooling or stirring [ 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Afterward, the desired pre-emulsion was sonicated using a sonicator probe (Bransonic, USA) in 7 cycles of 60 s with a rest time of 15 s between each cycle. Finally, the suspension was allowed to cool naturally at room temperature over 24 h, facilitating the formation of NLC/SLN without the need for external cooling or stirring [ 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…The results indicated that the entrapment efficiency increased up to 90.81±3.75%, and the NLC exhibited a tyrosinase inhibition rate of approximately 72%. Based on their findings, the researchers proposed that the formulated NLC could be efficiently utilized for sustained action on the epidermal layer of the skin, making it a promising option for skin brightening purposes [51] .…”
Section: Nlcs In Treating Hyperpigmentationmentioning
confidence: 99%